ANALISIS KRIMINOLOGI TERHADAP KEKERASAN ANAK DI LINGKUNGAN PESANTREN PERSPEKTIF HUKUM ISLAM: CRIMINOLOGICAL ANALYSIS OF CHILD ABUSE IN ISLAMIC BOARDING SCHOOLS PERSPECTIVE OF ISLAMIC LAW - Nurchaliq Majid (IAI DDI Mangkoso, 2022)
The main problem of this research is how to review the criminology of violence against children in the modern Tarbiyah Takalar Islamic boarding school? The main problem is then specified into several subproblems or research questions, namely: 1) What are the factors of violence against children in the perspective of criminology? This type of research is classified as qualitative with a criminological research approach. The data sources for this research are several literatures such as reference books, journals, and several supporting articles, and of course the case decision manuscripts that you want to study as the main reference material. The results of this study indicate that Law Number 23 of 2002 has very clearly regulated the provisions relating to violence against children. These provisions include the definition of children contained in chapter 1 general provisions, article 1 paragraph 1 of the child protection law, explaining that a child is someone who is not yet 18 (eighteen) years old, including children who are still in the womb. Likewise, the rights of children are explained in Article 1 paragraph 12 of the Child Protection Law which explains that children's rights are part of human rights that must be guaranteed, protected and fulfilled by parents, families, communities, governments, and the State. One of the rights of a child that must be fulfilled is the right to education and teaching, as stated in Article 9 paragraphs 1 and 2 of Law no. 23 of 2002 concerning child protection. concerning the phenomena of violence against children in the school environment which in recent years has seized our attention. Phenomena like this should be prohibited from happening in Indonesia, because the Indonesian Constitution number 23 of 2002 concerning child protection. Article 54 clearly states that children in and within the school environment must be protected from acts of violence committed by anyone. The implications of this research are; 1) The provisions of the Law on Child Protection should be emphasized even more, especially the issue of implementation and implementation. Because there is still a lot of violence against children, especially in the school environment that cannot be reached by the law. For teachers, the process of disciplining students should not and should not always use violence. Even if there is violence, it must go through stages or procedures that do not violate the rules. 2) the role of teachers and coaches is very important in implementing the law on child protection, so that in the future there will be no violence against children, especially in the school environment.